Impacts of resveratrol versus platelet-rich plasma for treatment of experimentally lithium-induced thyroid follicular cell toxicity in rats. A histological and immunohistochemical study. (2nd January 2019) - El-Mahalaway, Abeer M.; El-Azab, Nahla El-Eraky
ABSTRACT: Lithium (Li) is used for the treatment and prophylaxis of mental disorders, associated with many serious hazards. Resveratrol (RSV) has various beneficial therapeutic effects. Platelet-rich plasma (PRP) is a new promising curative tool. This study aimed to assess the impacts of RSV versus PRP on lithium-induced thyroid follicular cell toxicity in adult male rats. Forty-nine adult male rats were divided into four groups: group I: control rats; group II: lithium-treated rats; group III: lithium- and resveratrol-treated rats; group IV: lithium and PRP-treated rats. Thyroid specimens were taken and processed for histological and immunohistochemical methods. Morphometrical studies and statistical analysis were done. Group II showed distorted thyroid follicles, significantly increased collagen fibers, and highly positive P53 immunostaining ( P  < 0.01). Ultrastructural examination showed dilated rough endoplasmic reticulum and damaged mitochondria. Groups III and IV exhibited significant amelioration of the histological and electron microscopic changes mentioned previously. PRP remedy was more effective than RSV for treatment of Li-induced thyroid follicular cell toxicity.